Blood Pressure Trajectories for 16 Years and the Development of Left Ventricular Hypertrophy and Increased Left Atrial Size: The Korean Genome and Epidemiology Study. (18th July 2022) - Kim, Seong Hwan; Lee, Ju-Mi; Lee, Seung Ku; Shin, Chol; Park, Jae-Hyeong
Abstract : Background . Elevated single blood pressure (BP) measurement can be associated with the development of hypertension-mediated target organ damage including left ventricular hypertrophy (LVH) and left atrial (LA) enlargement (LAE). However, long-term patterns of BP and their effects on LVH and LAE are poorly understood. We evaluated the association between the BP trajectories and the presence of LVH and LAE. Methods . We analyzed a total of 2, 565 participants (1, 267 males, 47.8 ± 6.7 years old) from the first biennial examination (2001-2002) of the Korean Genome and Epidemiology Study. The presence of LVH and LAE was identified by echocardiography performed at the 8 th biennial examination (2015-2016). Latent mixture modeling was used to identify trajectories in mid-BP ((systolic BP + diastolic BP)/2) over time. Linear logistic regression was used for assessing BP trajectories with the outcomes. Results . We identified 4 distinct mid-BP trajectories: group 1 (lowest, 20.9%, n = 536), group 2 (36.2%, n = 928), group 3 (32.3%, n = 828), and group 4 (highest, 10.6%, n = 273). Compared with the lowest group, trajectories with elevated mid-BP had greater odds ratios having LVH and LAE by multivariable-adjusted regression models. Adjusted odd ratios for LVH were 2.033 (95% CI = 1.462–2.827, P < 0.001 ) for group 2, 3.446 (95% CI = 2.475–4.797, P < 0.001 ) for group 3, and 4.940 (95% CI = 3.318–7.356, P < 0.001 ) for group 4. Adjusted odd ratios for LAE were 1.200 (95% CI = 0.814–1.769, P = 0.358 ) for group 2, 1.599 (95% CI = 1.084–2.360, P = 0.018 ) for group 3, and 1.944 (95% CI = 1.212–3.118, P = 0.006 ) for group 4. Conclusions . Higher long-term mid-BP was an independent risk factor of cardiac structural changes such as LVH and LAE among middle-aged population.